Mechanism of leptin-NPY on the onset of puberty in male offspring rats after androgen intervention during pregnancy - Liu, Jingqi; Yuan, Yongting; Peng, Xingwang; Wang, Yuanyuan; Cao, Ruiyao; Zhang, Yun; Fu, Lianguo (Frontiers in Endocrinology, 2023)
Objectives: The time of onset of puberty has been increasingly earlier, but its mechanism is still unclear. This study aimed to reveal the mechanism of leptin and NPY in the onset of puberty in male offspring rats after androgen intervention during pregnancy. Methods: Eight-week-old SPF healthy male SD rats and 16 female SD rats were selected and caged at 1:2. The pregnant rats were randomly divided into the olive oil group (OOG) and testosterone group (TG), with 8 rats in each group. Olive oil and testosterone were injected from the 15th day of pregnancy, for a total of 4 injections. After the onset of puberty, the male offspring were anesthetized with 2% pentobarbital sodium to collect blood by ventral aorta puncture and decapitated to peel off the hypothalamus and abdominal fat. Serum testosterone (T), free testosterone (FT), dihydrotestosterone (DHT), dehydroepiandrosterone (DHEA), sex hormone binding globulin (SHBG), and leptin were detected by ELISA, and then the free androgen index (FAI) was calculated. The mRNA levels of androgen receptor (AR), estrogen receptor α (ERα), NPY, leptinR, and NPY2R in the hypothalamus and abdominal fat were detected by RT‒PCR. Protein expression levels of AR, ERα, NPY, leptinR, and NPY2R in the arcuate nucleus of the hypothalamus were detected by immunohistochemistry. Results: The time of onset of puberty was significantly earlier in the TG than in the OOG (P<0.05) and was positively correlated with body weight, body length, abdominal fat, and leptinR mRNA levels in adipose tissue in OOG (P<0.05), while it was positively correlated with serum DHT and DHEA concentrations and FAI and AR mRNA levels in the hypothalamus in the TG (P<0.05). The NPY2R mRNA level and protein expression levels of ERα, NPY2R, and leptinR in the TG were significantly higher than those in the OOG, while the protein expression levels of AR and NPY in the TG were significantly lower than those in the OOG (P<0.05). Conclusions: Testosterone intervention during pregnancy led to an earlier onset of puberty in male offspring rats, which may render the male offspring rats more sensitive to androgens, leptin, and NPY at the onset of puberty.